1998
DOI: 10.1016/s1010-7940(98)00147-x
|View full text |Cite
|
Sign up to set email alerts
|

Post cardiac surgery phrenic nerve palsy: value of plication and potential for recovery

Abstract: Prospective screening for PNP revealed an incidence in children younger than 1 year of 6%. Early plication substantially reduces the duration of ventilation, with its associated reduced morbidity and ICU stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 14 publications
4
62
0
1
Order By: Relevance
“…Respiratory condition is one of the most important factors influencing mortality and morbidity especially in infants. DP after cardiac surgery is an important complication with negative effects on pulmonary situation [1][2][3][4][5][6][7][8][9]. Reports of the prevalence of DP after cardiac operations in children vary from 0.3 to 12.8% [3, 6, 10-12, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Respiratory condition is one of the most important factors influencing mortality and morbidity especially in infants. DP after cardiac surgery is an important complication with negative effects on pulmonary situation [1][2][3][4][5][6][7][8][9]. Reports of the prevalence of DP after cardiac operations in children vary from 0.3 to 12.8% [3, 6, 10-12, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Diaphragmatic paralysis (DP) due to phrenic nerve injury after congenital cardiac surgery is an important respiratory complication resulting with respiratory insufficiency, lung infections, prolonged hospital stay time and even death [1][2][3][4][5][6][7][8][9]. It is accepted that procedures in congenital cardiac surgery are the major causes of DP with an incidence ranging from 0.3 to 12.8% [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A retrospective study by Dagan et al identified nine BDP cases among 3,214 children who had undergone cardiac surgery, resulting in an incidence of 0.28%. 13 Zhang et al reported four cases of BDP out of 47 patients with diaphragmatic paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…This timing is similar to that reported by other researchers. 12,13 In cases of BDP, ultrasonography and/or fluoroscopy findings are considered diagnostic. 5,9,10,[15][16][17][18] All BDP diagnoses in the current series were based on one of these radiological modalities.…”
Section: Discussionmentioning
confidence: 99%